Evaluation of Mechanical Properties and Wear Behavior of Aluminium-Red Mud Composite Synthesized By Powder Metallurgy. - Chinta, Neelima Devi; Selvaraj, N.; Mahesh, V. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
Red mud received from NALCO, Odisha, India has been subjected for sieve analysis and milled to 42 nanometers using high energy ball mill. Pure aluminium powder of 99.72% purity as matrix with red mud as reinforcement at 2%, 4%, and 6% weight fractions at micro as well as nano levels. Micro and nano structured red mud powders and pure aluminium are mixed in a V-blender, compacted at a pressure of 40 bar and samples are prepared by conventional sintering. The mechanical properties of Aluminium-Red mud micro and nano composites are evaluated with respect to hardness and compression strength. The experimental compression strength values are validated by Deform-2D software. An increase in hardness and compression strength is observed with increase in the amount of percentage weight fraction of Red mud. Wear characteristics are investigated using pin-on-disc wear testing machine and evaluated the prediction of optimal combination of pure aluminium and weight fraction of micro and nano structured red mud powder using Regression analysis. Highest wear resistance is observed for the test specimen with 42 nm size and 6% weight fraction of red mud powder at 600 RPM speed.